Empowerment of Ranah Singkuang Village Cadres in Making Shower Gel from Organic Patin Bone Gelatin - Rahimatul Uthia; Ira Oktaviani Rz; Fathunikmah Fathunikmah; Alexsander Yandra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community engagement is an implementation of previous research in which organic gelatin was made from Patin bones extracted using pineapple water. Gelatin is a derivative of collagen, which is a type of protein found in skin, bones and muscles. The source of gelatin can be obtained from Patin bones, where Riau Province is a province that produces quite a lot of Patin in Indonesia, as a source of gelatin. Kampar Regency also has potential for developing pineapple commodities. It has an average production of 875 tons/hectare to 1.6 tons/hectare. This is the basis for using pineapple skin as a gelatin extractor from Patin bones, so that the gelatin obtained later is healthy organic extract gelatin. As a downstream product, it is used to make shower gel as one of the downstream gelatin products developed in community engagement in Ranah Singkuang.